Behaviour of a joint between a U-shaped steel-concrete beam and a concrete-filled steel tubular column. (December 2020) - Heng, Piseth; Lepourry, Clemence; Somja, Hugues; Palas, Franck
Abstract: A new type of U-shaped steel-concrete beams (USCB) using L-angle shear connectors was recently proposed as an alternative solution for long-span structures. In a specific portal frame configuration used in a recent building, the USCB is connected to concrete-filled steel tubular columns by welded steel-concrete joints. The behaviour of these joints plays a crucial role in the global structural stability of the frame as much as that of the whole building. Due to the composite steel-concrete action within the joint, its design is not explicit nor available in design provisions. This paper has the objective to investigate the behaviour of this complex joint and propose a design model of the joint for practical engineers. An experimental campaign of two full-scale tests was carried out in order to determine the moment resisting capacity, the deformation capacity, the cracking patterns, and the failure mode of the joint. A finite element model of the test was also developed and validated against the experimental results to investigate more closely the load transfer mechanism and the propagation of plastification in the components of the joint. The stress map obtained from the FE model was afterwards used to define the geometry of the design model of the joint. This model was proposed based on the strut-and-tie method for the concrete part and the shear panel model for the steel part of the joint. The interesting feature of the design model is the inclusion of the load transfer mechanism of the forces between the steel and the concrete parts of the joint. Finally, a parametric study on the influence of steel detailing inside the joint using the FE model was carried out. It was found out that the initial solution can be simplified and optimised. Graphical abstract: Unlabelled Image Highlights: Behaviour of a joint between concrete-filled steel tubular columns and composite beams with u-shape steel profile. A design model of the joint that combines the steel part and the concrete part with the system of load transfer mechanism. The steel joint is modelled by shear panel model. Strut-and-tie model is adopted for the concrete part of the joint. The geometry of the strut-and-tie model is derived from the stress map obtained from the numerical simulation.